(untitled) (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2024)
This study aims to investigate the flexing phenomenon on social media exploring its position between financial education and ostentatious displays of wealth with a focus on its implications in criminal law aspects in Indonesia The research employed a qualitative methodology utilizing interviews with key stakeholders focus group discussions analysis of social media content and a comprehensive literature review Additionally the study incorporated comparative analysis with other Southeast Asian countries to provide regional context The results reveal a complex interplay of social legal and educational factors surrounding the flexing phenomenon Key findings include: 1 a significant divergence in perceptions of flexing among different stakeholders with influencers viewing it as inspirational while legal experts express concerns about potential legal scrutiny; 2 the effectiveness of flexing as an educational tool when balancing success stories with practical financial advice; 3 a notable knowledge gap among social media users regarding the legal implications of their online behavior; 4 growing concerns about the use of social media evidence in financial crime investigations; 5 the emergence of aspirational flexing among younger users raising ethical and potential legal issues; and 6 a shift in public perceptions of wealth and success due to constant exposure to luxury displays on social media The study concludes that while flexing can serve as a powerful educational tool it also presents significant legal risks and societal challenges that require a balanced approach to address effectively< p>